2018
DOI: 10.1126/science.aap8861
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic thrombopoietin is required for bone marrow hematopoietic stem cell maintenance

Abstract: Hematopoietic stem cell (HSC) maintenance depends on extrinsic cues. Currently, only local signals arising from the bone marrow niche have been shown to maintain HSCs. However, it is not known whether systemic factors also sustain HSCs. We assessed the physiological source of thrombopoietin (TPO), a key cytokine required for maintaining HSCs. Using knock-in mice, we showed that TPO is expressed by hepatocytes but not by bone marrow cells. Deletion of from hematopoietic cells, osteoblasts, or bone marrow mesenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 46 publications
3
103
0
Order By: Relevance
“…It has been speculated for a long time that hepatocytes might modulate monocyte BM 5 hematopoiesis and egress (Decker et al, 2018;Serbina et al, 2012). Here we show that food energy-sensing by a liver AMPK-PPARα pathway controls BM monocyte egress to the blood circulation.…”
Section: Discussionmentioning
confidence: 60%
“…It has been speculated for a long time that hepatocytes might modulate monocyte BM 5 hematopoiesis and egress (Decker et al, 2018;Serbina et al, 2012). Here we show that food energy-sensing by a liver AMPK-PPARα pathway controls BM monocyte egress to the blood circulation.…”
Section: Discussionmentioning
confidence: 60%
“…One of the most significant changes observed during the aging process is a decline in the overall function of endothelial cells (ECs), including the EC niche of the hematopoietic system (Das et al, 2018; El Assar et al, 2012; Le Couteur and Lakatta, 2010). An increasing body of evidence demonstrating functional interactions between the HSPC and its niche suggests that both local and systemic factors regulate HSPC function (Bowers et al, 2018; Crane et al, 2017; Decker et al, 2018; Lazzari and Butler, 2018; Pinho and Frenette, 2019). However, to date, most reports describing alterations in the aged hematopoietic compartment have focused on the cell-intrinsic properties of HSPCs.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was recently shown that HSCs did not rely on local Thpo production by the BM niche. 60 The cell-specific deletion of Thpo in megakaryocytes, osteoblasts, and mesenchymal stromal cells did not alter HSC stem cell potential, while Thpo depletion in liver cells had similar effects in HSCs as in Thpo −/− mice. Although the data indicate that the main source of Thpo to maintain steady-state hematopoiesis is the liver, changes in Thpo production in the local milieu under various stress conditions have not been investigated.…”
Section: Regulation Of Thpo Production and Mpl Expression For Hsc Maimentioning
confidence: 84%